Trinidad and Tobago : 2001 Article IV Consultation-Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Authorities of Trinidad and Tobago. (IMF Staff Country Reports; Country Report ;, 2001)
Trinidad and Tobago showed strong economic performance. Executive Directors welcomed this development, and emphasized the need to maintain strong fiscal and monetary policies, and accelerate structural reforms. They appreciated the proposals to include the state energy companies in the list of government assets, and noted the restructuring of the sugar sector. They mentioned Trinidad and Tobago's growing importance as a regional financial center, and commended the supervision of the financial system in line with international standards, and the good quality of statistics.